The Internalization of Tri-N Tamansiswa Teaching Principle in Primary School Teacher Education Department - C. Indah Nartani; Kristi Wardani; Biya Ebi Praheto (Universitas Riau, 2020)
This research aims to explain the internalization of Tri-N Tamansiswa Teaching of Primary School Teacher Education Department (PGSD) at Sarjanawiyata Tamansiswa University. The subjects of this research are the Study Program Chairman, lecturers and college students. As for the research object was the internalization of the Tri-N teaching of Tamansiswa. The data collection was done by observation method, interview and documentation. The research results of shows that the role of the Study Program Chairman is crucial to the internalization of the Tri-N Tamansiswa teaching in strengthening students pedagogical competence. It is because the Study Program Chairman has the authority to make policy in the internalization of Tamansiswa teaching. A pattern or model of the internalization of Tri-N Tamansiswa Teaching is known that derives from the preparation of the vision and the mission continued with the establishment of the study program policy related to the implementation of Tamansiswa teaching and integration of Tamansiswa teaching especially Tri-N in the curriculum, Semester Lesson Plan, and the learning process. In addition, the Tri-N Tamansiswa teaching has also been applied by the lecturer in classroom teaching and learning so it accustoms college students to be teacher candidate who based on Tamansiswa teaching.